Implications of Birth-Dose Vaccination against Hepatitis B Virus in Southeast Asia - Fazle Akbar, Sheikh Mohammad; Al Mahtab, Mamun; Begum, Ferdousi; Hossain, Shaikh A. Shahed; Sarker, Sukumar; Shrestha, Ananta; Khan, Md. Sakirul Islam; Yoshida, Osamu; Hiasa, Yoichi (MDPI, 2022)
This article was published in the Vaccines by MDPI [© 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).] and the definite version is available at: https://doi.org/10.3390/vaccines9040374 The Journal's website is at: https://www.mdpi.com/2076-393X/9/4/374